Investigation on electron contamination of LINAC at different operating voltages using particle heavy ion transport code system (PHITS) - Bilalodin, Bilalodin; Haryadi, Aris; Sardjono, Yohannes; Kasesaz, Yaser (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2022)
Research has been carried out to investigate the occurrence of secondary electron contamination in a linear accelerator (LINAC) machine. The research was conducted in a simulation using a Monte Carlo-based simulator, namely Particle and Heavy Ions Transport code System (PHITS). The simulation of the occurrence of secondary electron contamination was carried out based on the model of the LINAC Electa head that is operated at voltages of 6, 8, 10, 15, 18, and 25 MV, using a field area of 10 X 10 cm and SSD 100 cm. The simulation results show that electron contamination occurs due to the interaction of X-ray photons with the components of the LINAC head, namely the primary collimator, flattening filter, and secondary collimator. The secondary electron contaminants generated by the LINAC head components spread through the water phantom. The higher the operating voltage, the higher the secondary electron flux produced. The secondary electron contamination dose calculated in the water phantom shows that the higher the LINAC voltage, the higher is the dose received in the phantom.